Allelopathy Potential of Jamaican Cherry (Muntingia calabura L.) Leaf Extract in Inhibiting the Germination and Growth of Amaranthus spinosus L. Weed - Rita Wahyuningtyas; Sri Darmanti; Endah Dwi Hastuti (Institut Pertanian Bogor, 2025)
This study examined the effects of an aqueous extract of Muntingia calabura L. leaves on the inhibition of germination and growth of Amaranthus spinosus. The study used a single-factor Completely Randomized Design, namely, the concentration of extract with treatment levels of 0, 2, 4, and 6% for germination and 0, 10, 20, and 30% for growth. Data were analyzed using Analysis of Variance and Duncan's Multiple Range Test at a confidence level of 95%. The results showed that treatment with the aqueous of leaf extracts decreased the percentage of germination, germination index, radicle, and stem length of the sprouts and slowed the germination time. During growth, it decreased the plant height, number of leaves, fresh weight, dry weight, and extended flowering time. The higher the concentration of the extract, the greater the decrease in the germination and growth of the weed. At concentrations of 10 and 20%, the contents of chlorophyll a, chlorophyll b, and carotenoids increased, but at a concentration of 30%, the contents began to decrease. At a concentration of 6%, germination decreased by 75%, germination index decreased by 87.47%, sprout length decreased by 27.51%, radicle length decreased by 26.20%, and germination time increased by 14.74%. At a concentration of 30%, the plant height was 6.48%, the number of leaves was 38.13%, the fresh weight was 20.64%, and the dry weight was 18.36%; however, the flowering time increased by 40%. Keywords: Allelochemicals, germination, growth, inhibition, Muntingia calabura L